Eastern European Courage through Game Art: The First Two Years of the Game Art Programme at University of Theatre and Film Arts, Budapest (2019-2021) - Radák, Judit (Gamevironments, 2021)
This case study aims to show that, for game use in education, it is not sufficient for transferred knowledge to simply become part of a game, but that personal experience is also necessary. Knowledge transfer needs a supporting context that help provide intrinsic motivations, as well as helping learners to have some sort of flow experience. All of this also relates to a secondary research objective presented in this report, which is to describe the inception and conceptual approach of the only Master’s programme in Hungary, building on courses relating to video game design. These courses rests on two main pillars: the contemplation of social issues, and cooperation between students. Several unexpected events created the context for this case study: the sudden death in September 2019 at the launch of the MA course of László Rajk, who initiated the course; the start of the Covid-19 pandemic in March 2020; and then at the end of the semester a political decision that put in question the autonomy of the university, leaving students and teaching staff alike in an uncertain situation. All of these circumstances had a significant impact on teaching in the programme, as well as on our students’ learning processes. In this contribution, we present the lived experience we acquired in this special situation and how this is closely related to the investigation of the extent to which personal experience shapes personal, intrinsic, motivation in game-oriented education.